2002
DOI: 10.1002/ptr.933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of  Ginkgo biloba extract on β‐adrenergic receptors in different rat brain regions

Abstract: The effect of oral administration of Ginkgo biloba extract at a dose of 90 mg/kg for 7 consecutive days on rat brain beta-adrenergic receptors in the frontal cortex, hippocampus, striatum and hypothalamus was studied. Ginkgo biloba treatment induced a significant decrease in the density (B(max)) of beta-adrenoreceptors in the frontal cortex and hippocampus. It has been suggested that modulation of the beta-adrenergic system is implicated in the favourable effects of Ginkgo biloba extracts on learning and memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Adra2b and Adra2c play roles in learning and memory, reinforcement, sleep-wake cycle regulation, affective psychoses, and aggression regulation (Shishkina and Dygalo, 2002;de Quervain et al, 2007). It has been reported that another extract from Ginkgo biloba, GK 501, also increases the density of Adr in the cortex and hippocampus (Hadjiivanova Ch and Petkov, 2002). Hrh3 is the recently discovered G-protein-coupled histamine receptor.…”
Section: Discussionmentioning
confidence: 97%
“…Adra2b and Adra2c play roles in learning and memory, reinforcement, sleep-wake cycle regulation, affective psychoses, and aggression regulation (Shishkina and Dygalo, 2002;de Quervain et al, 2007). It has been reported that another extract from Ginkgo biloba, GK 501, also increases the density of Adr in the cortex and hippocampus (Hadjiivanova Ch and Petkov, 2002). Hrh3 is the recently discovered G-protein-coupled histamine receptor.…”
Section: Discussionmentioning
confidence: 97%
“…Although most studies seem to show a greater effect in aged and/or cognitively impaired animals, there are some studies showing positive effects on cognitive performance in young rodents (17,18,208,209) (Table 2). While the mechanisms underlying the neuroprotective actions of GB are unclear, there is some evidence showing that GB extract can regulate the levels of neurotransmitters, such as serotonin (210) , influence neurotransmitter receptors (211)(212)(213) , regulate structural changes in hippocampal circuitry (19) , affect neuronal excitability (214) and trigger neurogenesis in the hippocampus (215) . In addition, GB-supplemented mice show an up-regulation of several neuromodulatory elements, such as a-amino-3hydroxy-5-methyllisoxazole-4-propionic acid-type glutamate receptors and microtubule-associated Tau (216) .…”
Section: Ginkgo Bilobamentioning
confidence: 99%
“…Indeed, in the United States and particularly in Europe, G biloba is perhaps the most widely used herbal treatment consumed specifically to prevent age-related cognitive decline 2. Putative mechanisms of action on brain functioning include vascular effects such as cerebral vasorelaxation and reduction of blood viscosity,3,4 reduction of oxygen free radicals,5 and neurotransmitter system effects 6,7. Moreover, some in vitro studies indicate that G biloba may inhibit amyloid aggregation, suggesting another mechanism of preventing or delaying cognitive decline associated with Alzheimer disease 8…”
mentioning
confidence: 99%
“…2 Putative mechanisms of action on brain functioning include vascular effects such as cerebral vasorelaxation and reduction of blood viscosity, 3,4 reduction of oxygen free radicals, 5 and neurotransmitter system effects. 6,7 Moreover, some in vitro studies indicate that G biloba may inhibit amyloid aggregation, suggesting another mechanism of preventing or delaying cognitive decline associated with Alzheimer disease. 8 To date, adequately powered, longerduration clinical trials testing the effect of G biloba on the rate of cognitive decline in aging have been lacking.…”
mentioning
confidence: 99%